2013
DOI: 10.7314/apjcp.2013.14.5.3229
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel BRCA2 and CHEK2 A-C-G-C Haplotype in Turkish Patients Affected with Breast Cancer

Abstract: Background: Many breast cancers are caused by certain rare and familial mutations in the high or moderate penetrance genes BRCA1, BRCA2 and CHEK2. The aim of this study was to examine the allele and genotype frequencies of seven mutations in BRCA1, BRCA2 and CHEK2 genes in breast cancer patients and to investigate their isolated and combined associations with breast cancer risk. Methods: We genotyped seven mutations in BRCA1, BRCA2 and CHEK2 genes and then analyzed single variations and haplotype associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
(29 reference statements)
2
5
0
Order By: Relevance
“…So the heterozygous AG genotype showed a statistically signi icant protective effect 16%(OR= 0.7619, 95% CI OR= (0.273 -2.125), PF=0.047), compared with control group they have (0% GG, 80% AA and 20% AG) . this result have similarity with results of (Haytural, 2013), she tested (310) patients with breast cancers were recruited from different public and private hospitals of Bangladesh and as controls (250) Bangladeshi women, and found GG genotype increase the risk of malignant tumor in breast (OR=4.9, 95% CI=0.59 to 41.09, p=0.14). So our result that is consistence with study (Hansa et al, 2012), who study on 106 consecutive breast cancer patients who were admitted to Istanbul Training and Research Hospital, Department of General Surgery and, they found GG responsible for risk to breast cancer (OR=8.54, 95% CI; 1.07-68.27).…”
Section: -Demographic Characteristicssupporting
confidence: 72%
“…So the heterozygous AG genotype showed a statistically signi icant protective effect 16%(OR= 0.7619, 95% CI OR= (0.273 -2.125), PF=0.047), compared with control group they have (0% GG, 80% AA and 20% AG) . this result have similarity with results of (Haytural, 2013), she tested (310) patients with breast cancers were recruited from different public and private hospitals of Bangladesh and as controls (250) Bangladeshi women, and found GG genotype increase the risk of malignant tumor in breast (OR=4.9, 95% CI=0.59 to 41.09, p=0.14). So our result that is consistence with study (Hansa et al, 2012), who study on 106 consecutive breast cancer patients who were admitted to Istanbul Training and Research Hospital, Department of General Surgery and, they found GG responsible for risk to breast cancer (OR=8.54, 95% CI; 1.07-68.27).…”
Section: -Demographic Characteristicssupporting
confidence: 72%
“…185delAG mutation in BRCA1 was detected in only one patient with hereditary breast ovarian cancer syndrome from Turkish population 30 . Like our results, 6174delT mutation in BRCA2 gene were not detected in any of the studies investigating the frequencies of common BRCA1 and BRCA2 gene mutations in breast/ovarian cancer patients in Turkish population 15,[17][18][19][20][21][22][23][24]30 .…”
Section: Discussionsupporting
confidence: 50%
“…These gene mutations also have been studied in other populations in several studies [14][15][16] . In previous studies, the BRCA1 5382insC mutation has been detected in breast/ovarian cancer patients from Turkish population 15,[17][18][19][20][21][22][23][24] . However, we couldn't detect this mutation any of our early-onset breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations